China’s new five year plan and its economic policy changes - Munkhuu, Erdenebayar (Journal of International Studies, 2021)
In accordance with longstanding tradition, China approved its 14th Five-Year National Plan for Economic and Social Development in 2021-2025 in March this year. The national plan emphasizes innovation, production, technology, and security, and sets a long-term goal for 2035. The key to the successful implementation of the national plan is to expand its domestic demand, which will be the main driver of economic growth in the future. However, there are several challenges China may face in implementing its national plan such as insufficient incomes of households, ineffective use of resource, global pandemic and China-U.S. rivalry. The first part of the article outlines the main objectives, strategies, and characteristics of China’s new five-year national plan, the second part analyzes the changes in the country’s economic development policy, and the third part discusses the challenges and feasibility of the plan. In the final part, the author shares his views on the potential implications of China’s new national plan on the Mongolian economy and the issues to be addressed. БНХАУ-ын шинэ таван жилийн төлөвлөгөө, эдийн засгийн бодлогын өөрчлөлт Хураангуй: БНХАУ уламжлалт ёсоороо энэ оны 3 дугаар сард 2021-2025 онд эдийн засаг, нийгмийг хөгжүүлэх XIV таван жилийн төлөвлөгөөгөө баталлаа. Уг төлөвлөгөө шинэтгэл, үйлдвэрлэл, технологи, аюулгүй байдлыг чухалчилж, мөн 2035 оныг хүртэлх урт хугацааны зорилтыг дэвшүүлснээрээ онцлог байна. Төлөвлөгөөгөө амжилттай хэрэгжүүлэх түлхүүр бодлого нь дотоодын зах зээлийг эрчимжүүлж эдийн засгийн өсөлтийн үндсэн хөдөлгөгч хүч болгох бөгөөд өрхүүдийн орлого хангалттай өндөр бус, нөөц ашиглалтын үр өгөөж тааруу, цар тахал, Хятад Америкийн сөргөлдөөн зэрэг багагүй сорилт тулгарч буй. Энэхүү өгүүллийн эхний хэсэгт Хятадын шинэ таван жилийн төлөвлөгөөний голлох зорилт, стратеги, онцлогийг дурдаж, хоёрдугаар хэсэгт тус улсын эдийн засгийн хөгжлийн бодлогод гарч буй өөрчлөлтөд дүн шинжилгээ хийн, гуравдугаар хэсэгт тулгарч буй сорилт, биелэгдэх боломжийн талаар авч үзэж, төгсгөлд нь Монгол Улсын эдийн засагт үзүүлж болох нөлөө, анхаарах асуудлын тухайд санал бодлоо хуваалцлаа. Түлхүүр үг: XIV таван жилийн төлөвлөгөө, хос эргэлт стратеги, сорилт ба боломж, нөлөө